2004
DOI: 10.1084/jem.20040942
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4–Ig Activates Forkhead Transcription Factors and Protects Dendritic Cells from Oxidative Stress in Nonobese Diabetic Mice

Abstract: Prediabetes and diabetes in nonobese diabetic (NOD) mice have been targeted by a variety of immunotherapies, including the use of a soluble form of cytotoxic T lymphocyte antigen 4 (CTLA-4) and interferon (IFN)-γ. The cytokine, however, fails to activate tolerogenic properties in dendritic cells (DCs) from highly susceptible female mice early in prediabetes. The defect is characterized by impaired induction of immunosuppressive tryptophan catabolism, is related to transient blockade of the signal transducer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 55 publications
4
130
2
Order By: Relevance
“…The direct effect of abatacept binding to CD80/86 on APCs remains a topic of controversy (37,38,(48)(49)(50). While some studies have demonstrated that CTLA-4Ig induced the up-regulation of IDO in DCs, which subsequently modulated T cell activation, our data and other transcriptional data have failed to confirm this (37,38).…”
Section: Discussioncontrasting
confidence: 61%
“…The direct effect of abatacept binding to CD80/86 on APCs remains a topic of controversy (37,38,(48)(49)(50). While some studies have demonstrated that CTLA-4Ig induced the up-regulation of IDO in DCs, which subsequently modulated T cell activation, our data and other transcriptional data have failed to confirm this (37,38).…”
Section: Discussioncontrasting
confidence: 61%
“…16,17 In addition, the induction of antigenspecific T-cell differentiation or activation may be the critical function of DCs stimulated by DNA vaccines. 24 Thus, we proceeded to examine whether Foxo3 shRNA-transfected DCs can affect antigen-specific T-cell differentiation.…”
Section: Silencing Of Foxo3 Facilitated Dc-induced Ag-specific T-cellmentioning
confidence: 99%
“…In particular, activation of Foxo3 in T cells leads to growth suppression and apoptosis, indicating the vital role of Foxo3 in maintaining T-cell homeostasis and in restraining T-cell activity. [13][14][15] Furthermore, Fallarino et al 16 reported that the activation of Foxo3a is essential for the suppression of DC function following treatment with cytotoxic T lymphocyte-associated antigen 4 (CTLA-4)-immunoglobulin, a soluble form of CTLA-4. Additionally, Dejean et al 17 demonstrated that deficiency in Foxo3 lead to an expansion of the antigen-specific effector T-cell population following viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…2007. 37: 876-879 mechanism of IDO induction by a tolerogenic ligand, autocrine IFN-a will have an obligatory role in IDO induction (perhaps due to a required STAT1 function), and IFN-c from whatever source may or may not contribute to a sustained effect on IDO depending on environmental factors; in general DC terms, however, regulation of functional IDO is complex, is cell-type specific [2], and it involves interference with cytokine signaling [16] and transcription factor activity [17], modulation of continuous inhibitory effects on IDO function [13,18], and post-translational modifications of IDO itself [19].…”
Section: How Type I/ii Ifn Regulate Idomentioning
confidence: 99%
“…Transcriptional regulation of type I IFN genes in pDC is controlled mainly by IFN regulatory factor (IRF)3 and/or IRF7, and their respective promoters contain binding sites for several transcription factors [8]. CTLA-4 engagement of B7 in a subset of splenic DC, which share the CD8a marker with CD19 + DC, will activate factors that up-regulate a multiplicity of genes transcriptionally [15,17]. It is possible that in addition to the possible ancillary role of IFN-c production, or that of preformed IDO as a means of its own de novo induction, B7 ligation by CTLA-4 initiates a cascade of signaling events that culminate in the sequential activation of a set of genes and that the products of these genes might represent the molecular arrangement whereby a self-regulated response takes place.…”
Section: Cd19 + DC Exercise Self Controlmentioning
confidence: 99%